PERANCANGAN KOMIK SABAI NAN ALUIH - TERESIA, Drs. Syafwan, M.Si, Drs. H. Ismanadi Uska (DEKAVE : Jurnal Desain Komunikasi Visual, 2013)
The purpose of this design is to create Sabai nan Aluih comics as one of the efforts to preserve one of the folklores of West Sumatera. The data source of this design is the novel book of Sabai nan Aluih, authorized by Sutan Sati. Sabai nan Aluih comics were created using manual and digital method. This design produces the comics for Sabai nan Aluih adapted to Indonesian teenagers, especially teenagers in Padang city. Keywords: Padang city, Sabai nan Aluih, Comic